PENGARUH LATIHAN PITCHING SLINGSHOT JARAK TETAP DAN BERTAHAP TERHADAP HASIL PITCHING SOFTBALL MAHASISWA SEMESTER 4 PJKR UNWAHAS TAHUN 2017/2018 - Noviantoro Dwi Nugroho; Kardiyono Kardiyono; Yudhi Purnama (LP2M, 2018)
The purpose of this research is to know : The effect of constant range on the pitching slingshot exercise to the pitching softball result. The effect of gradual range on the pitching slingshot exercise to the pitching softball result. The different effect between constant and gradual range of pitching slingshot exercise against the pitching softball exercise. Based on the result of the constant range of pitching slingshot exercise data calculation obtained average score of pretest 7,91 points and posttest 12,91 points with probability value of (p)=0,000 (<0,05) there is efect on constant pitching slingshot exercise. Meanwhile, calculation of gradual pitching slinghsot exercise obtained average score of pretest 7,916 points and posttest 14,333 points with probability (p)=(0,000) (<0,05) there is effect on gradual pitching slingshot exercise. Calculation from both two exercise methods obtained average score of 12,91 points and 14,333 points, there is significant efect difference between the two excercise against the pitching softball result with conclusion on the effect of gradual range is higher with precrntage of 53,46%, while gradual pitching slingshot exercise only obtained 41,66%.Key Word : Pitching Slingshot exercise, Pitching Softball exercise